The evaluation of DLCO changes in patients with relatively higher lung shunt fractions receiving TARE - TUROĞLU, HALİL TURGUT; ÖZGÜVEN, SALİH (My University, 2022)
Objective Transarterial radioembolization (TARE) with Yttrium-90 (90Y) labeled microspheres is an efective locoregional treatment option for patients with primary and metastatic liver cancer. However, TARE is also associated with radiationinduced lung injury due to hepatopulmonary shunting. If a large proportion of the injected radionuclide microspheres (more than 15%) is shunted, a rare but lethal complication may develop: radiation-induced pneumonitis (RP). Difusion capacity of the lungs for carbon monoxide (DLCO) is a valuable test to assess lung function and a decrease in DLCO may indicate an impairment in gas exchange caused by the lung injury. Some previous researches have been reported the most consistent changes in pulmonary function tests after external beam radiotherapy are recorded with DLCO. This study aimed to examine the changes in DLCO after TARE with glass microspheres in newly treated and retreated patients with relatively higher lung shunt fractions. Methods We prospectively analyzed forty consecutive patients with liver malignancies who underwent lobar or superselective TARE with 90Y glass microspheres. DLCO tests were performed at baseline and on days 15, 30, and 60 after the treatment. All patients were followed up clinically and radiologically for the development of RP. Results A statistically significant decrease was found in the DLCO after the first treatment (81.4 ± 13.66 vs. 75.25±13.22, p=0.003). The frequency of the patients with impaired DLCO at baseline was signifcantly increased after the frst treatment (37.5 vs 57.5% p<0.05). In the retreated group (n=8), neither the DLCO (71.5±10.82 vs. 67.50±11.24, p=0.115) nor the frequency of patients with impaired DLCO (25 vs 25%, p=1) did not signifcantly change. Also, the change in DLCO values did not signifcantly correlate with lung shunt fraction, administered radiation dose, and absorbed lung dose after the frst and second treatments (p>0.05 for all). None of the patients developed RP. Conclusion Our study showed that a signifcant reduction in DLCO after TARE may occur in patients with relatively higher lung shunt fractions. Further studies with larger sample sizes are needed to better investigate the changes in DLCO in patients with high lung shunt fractions.